KEBIJAKAN PENGELOLAAN WILAYAH PERBATASAN DAN TANTANGANNYA: STUDI KOMPARASI WILAYAH PERBATASAN AUSTRALIA, LAOS, DAN INDONESIA - Aris Sarjito (JURNAL PELITA KOTA, 2023)
Border area management policies are important nowadays in facing various challenges faced by a country. This study aims to evaluate border area management policies in three different countries, namely Australia, Laos, and Indonesia, and their challenges in implementation. This study was conducted using a qualitative approach and a comparative method to compare border management policies in three countries. The data was obtained through literature study, as well as using policy analysis to assess implemented policies. The results of this study indicate that the three countries studied have different challenges in implementing border area management policies in their countries. Australia has relatively good policies in managing its border areas but still faces challenges with the refugee crisis and illegal migration. Laos has challenges in building infrastructure in its border areas and has a limited budget to manage its border areas. Meanwhile, Indonesia has challenges in terms of corruption, lack of budget, and lack of coordination between institutions in managing its border areas In facing these challenges, the three countries need to coordinate between agencies and use advanced technology in managing regional borders, as well as increasing community participation in managing regional borders. In addition, the border area management policies that are made need to be more contextual and fairer to address the challenges faced by each country.